Analysis of Public Satisfaction Levels Using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA): (Case Study: Public Satisfaction Survey on Services at the Pontianak City Inspectorate) - Afifah Diah Afianti; Pitriani (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Universitas Pamulang, Indonesia, 2025)
Public service delivery serves as a primary indicator of successful governance that emphasizes accountability, transparency, and citizen satisfaction. Poor-quality public services can diminish public trust in governmental performance and hinder the realization of good governance. This study aims to analyze the level of public satisfaction with services provided by Inspectorate of Pontianak City during the second semester of 2024 using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The CSI method is employed to measure overall satisfaction levels, whereas the IPA method is utilized to evaluate service attributes more comprehensively by comparing the importance and performance of each attribute and categorizing them into the IPA quadrants. The findings indicate that the overall public satisfaction level falls within the “very satisfied” category, with a CSI score of . This result reflects that the community generally perceives the quality of services delivered by Inspectorate of Pontianak City as highly satisfactory and able to meet user expectations. Furthermore, the IPA results reveal several attributes that require priority improvement, namely requirements, service completion time, service products, and staff competence, all of which fall into Quadrant I (high importance but low performance). These attributes are considered highly important by the public, yet their performance still requires enhancement to achieve optimal service delivery. Meanwhile, the attributes of service fees/tariffs, procedures, staff behavior, and complaint handling fall within Quadrant II (maintain performance), as they demonstrate strong performance and high importance, thus necessitating continued consistency.